Immunocytochemical analysis of glutamate and GABA in hippocampus of genetic absence epilepsy rats (GAERS) - (:unkn) unknown (ELSEVIER SCIENCE BV, 2003)
In the present study, we used an immunocytochemical technique at the electron microscopic level to determine if there are changes in the glutamate and GABA neurotransmitter content of the hippocampus of genetic absence epilepsy rats from Strasbourg (GAERS). We also investigated if there was mossy fiber reorganization. After perfusion fixation. brains were removed and cryostat sections were stained according to the neo-Timm's procedure. High-resolution electron microscopy was used for ultrastructural examination of the hippocampus of GAERS and non-epileptic control Wistar animals. For ultrastructural and immunocytochemical studies, ultrathin-cut sections were obtained and immunolabeled with anti-glutamate and anti-GABA antibodies. The number of gold particles per nerve terminal was counted and the area of the nerve terminal was determined using the program NIH Image Analysis. No mossy fiber sprouting was detected in the hippocampus of GAERS. GABA and glutamate immunoreactivity were observed in the mossy fiber terminals of both the control and GAERS groups. Glutamate density in the CA3 region of GAERS hippocampus was found to be significantly increased compared to the control group. However, there was no difference in the GABA density of nerve terminals and in areas of GABAergic and mossy terminals between GAERS and the control group. The difference in glutamate level may merely be due to strain differences between the GAERS strain and the original Wistar strain or it is also possible that it appears after seizures have started. Published by Elsevier B.V.
Keywords: GAERS; hippocampus; neo-Timm's; ultrastructure; glutamate; GABA; MOSSY FIBERS; FASCIA DENTATA; GRANULE CELLS; SYNAPSES; NEURONS; ZINC; DECARBOXYLASE; TERMINALS; SEIZURES; REGION